Differential Offending as Predicted by the Dark Triad - Helm, Farzad A. (Criminal justice and behavior, 2025)
Psychopathy is a risk factor in offending. However, there are additional traits associated with interpersonal harm that are understudied in incarcerated populations. We examined associations between the Short Dark Triad (SD3; Machiavellianism, narcissism, psychopathy) and three types of past and current offenses (drug, violent, non-violent/non-drug) in an incarcerated Iranian sample of men and women. For women, the SD3 factor analytic results had poor fit and uninterpretable psychometric properties. However, for men, the factor analytic results were sufficient and demonstrated clear separation among the three subscales. Among men, results demonstrated that psychopathy and narcissism were positively associated with current violent offenses, whereas Machiavellianism was negatively associated. Psychopathy was the only predictor of current drug offenses and Machiavellianism was the only predictor of current non-violent/non-drug offenses. Taken together, the findings demonstrate that the Dark Triad predict distinct types of offenses among men and the SD3 is effective for assessing incarcerated populations.